TRENDS OF MODE CHOICE AND PROMOTION OF SUSTAINABLE TRANSPORTATION IN MEGA CITY OF DEVELOPING COUNTRIES: A CASE STUDY FOR KARACHI - Syed Muhammad NOMAN; Afzal AHMED; Mohd Khairul Afzan Mohd LAZI; Uneb GAZDER (Scientific Journal of Silesian University of Technology. Series Transport)
The aim of this research is to explore the current urban transportation system of a megacity, Karachi. It was done by analyzing the Public Transport (PT) route network and commuter’s mode choice along with mode share. Four major arterials were selected for the study. Data was collected through field surveys and questionnaire-based survey. PT system of Karachi mainly consists of buses and minibuses. It was found that PT has 16% share in mode choice of Karachi’s travelers, which is less than most of the metropolitan cities in the world, and it has been decreasing constantly over the years. Most of the private vehicle users consider PT to be inefficient and uncomfortable. However, there is a willingness to use PT modes if they can provide at affordable prices. The current PT users are captive and women riders, which are bound economically or culturally to use these modes. Other sustainable modes of transport such as car-sharing and walking do not have significant share in mode share as well. Focused awareness campaigns for promotion of these modes should also be initiated.